Anabolic steroid use: Patterns of use and detection of doping - Graham, M. R.; Davies, B.; Grace, F. M.; Kicman, A.; Baker, J. S. (Sports Medicine, 2008)
Anabolic-androgenic steroids (AAS) were the first identified doping agents that have ergogenic effects and are being used to increase muscle mass and strength in adult males. Consequently, athletes are still using them to increase physical performance and bodybuilders are using them to improve size and cosmetic appearance. The prevalence of AAS use has risen dramatically over the last two decades and filtered into all aspects of society. Support for AAS users has increased, but not by the medical profession, who will not accept that AAS use dependency is a psychiatric condition. The adverse effects and potential dangers of AAS use have been well documented. AAS are used in sport by individuals who have acquired knowledge of the half-lives of specific drugs and the dosages and cycles required to avoid detection. Conversely, they are used by bodybuilders in extreme dosages with the intention of gaining muscle mass and size, with little or no regard for the consequences. Polypharmacy by self-prescription is prevalent in this sector. Most recently, AAS use has filtered through to 'recreational street drug' users and is the largest growth of drugs in this subdivision. They are taken to counteract the anorexic and cachectic effects of the illegal psychotropic street drugs. Screening procedures for AAS in World Anti-Doping Agency accredited laboratories are comprehensive and sensitive and are based mainly on gas chromatography-mass spectrometry, although liquid chromatography-mass spectrometry is becoming increasingly more valuable. The use of carbon isotope mass spectrometry is also of increasing importance in the detection of natural androgen administration, particularly to detect testosterone administration. There is a degree of contentiousness in the scenario of AAS drug use, both within and outside sport. AAS and associated doping agents are not illegal per se. Possession is not an offence, despite contravening sporting regulations and moral codes. Until AAS are classified in the same capacity as street drugs in the UK, where possession becomes a criminal offence, they will continue to attract those who want to win at any cost. The knowledge acquired by such work can only assist in the education of individuals who use such doping agents, with a view to minimizing health risks and hopefully once again create a level playing field in sport.